Fragmentation of Social Solidarity in the Platform Economy Era: A Sociological Study on the Individualization of Work in Digital Society - Randi, Randi (Socious Journal, 2026)
The rapid expansion of the platform economy has transformed labor structures and reshaped social relations within digital society. While platform-based work offers flexibility and entrepreneurial narratives, it simultaneously intensifies algorithmic control and individualization, raising concerns about the fragmentation of social solidarity. This study aims to analyze how the individualization of work in the platform economy contributes to the transformation and fragmentation of social solidarity, while also examining the emergence of new forms of digital collective identity. A qualitative sociological approach was employed using multiple case studies of ride-hailing drivers, couriers, and food delivery workers. Data were collected through in-depth interviews, digital ethnography of online worker communities, and document analysis of platform policies. The findings reveal that algorithmic governance, performance ratings, and the “partner” ideology weaken collective labor identity and foster competition and isolation. However, workers simultaneously construct digital communities through social media and messaging platforms, enabling episodic and hybrid forms of solidarity. The study concludes that the platform economy produces a paradoxical dynamic: it fragments traditional social solidarity while generating new digitally mediated collective formations. Social cohesion in digital capitalism is therefore not eliminated but reconfigured within evolving socio-technical structures.